The impact of the internal hydrophobisation on the properties and durability of cement-based materials - Materak Kalina; Wieczorek Alicja; Koniorczyk Marcin (MATEC Web of Conferences)
The presented study investigates the impact of internal hydrophobization by using an organosilicon admixture based on triethoxyoctylsilane on the properties and durability of cement-based materials. Internal hydrophobization is an effective method for enhancing water resistance by incorporating hydrophobic agents directly into the cement matrix. The research evaluates the effects of this technique on cement hydration and microstructure of cement paste, as well as, capillary water absorption, compressive strength, resistance to freeze-thaw cycles and water penetration under pressure in concrete. The results indicate that the hydrophobic admixture influences cement hydration by reducing heat release and modifying pore structure. Compared to surface hydrophobization, internal hydrophobization in concrete provides long- lasting protection against water penetration, maintaining effectiveness even after 150 freeze-thaw cycles. However, excessive admixture dosage negatively affects mechanical properties, leading to excessive decrease in compressive strength. The study demonstrates that a carefully controlled dosage of hydrophobic admixture can significantly enhance the durability of concrete while minimizing negative impacts on the other properties of hardened material. These findings highlight the advantages of internal hydrophobization over traditional surface treatments, making it a promising approach for improving the longevity and performance of cementitious materials in aggressive environmental conditions.